APPLICATION INVENTORY DATA COLLECTION WITH CV ARTA BOGA VISUAL BASIC 6.0 PROGRAMMING - Sugiarto Sugiarto; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 2004)
Inventory data collection using Visual Basic 6.0 application program, will accelerate in the data collection process on the part of administration and can assist in preparing reports. by changing the files in the form of the worksheet into an organized fields will facilitate the process of data search.